Characterization of defect states in Mg-doped GaN-on-Si p+n diodes using deep-level transient Fourier spectroscopy. (8th December 2020) - Lechaux, Y; Minj, A; Méchin, L; Liang, H; Geens, K; Zhao, M; Simoen, E; Guillet, B
Abstract: Mg-doped GaN-on-Si p + n diodes have been fabricated and characterized by static electrical and deep-level transient Fourier spectroscopy (DLTFS) measurements. From static capacitance-voltage ( C–V ) and current–voltage ( I–V ) characteristics, we estimated the diffusion barrier of the p + n diode close to the GaN band gap at room temperature. The temperature dependence of the capacitance showed freeze-out effect of the Mg-dopants at 200 K. From DLTFS measurements for various reverse bias and pulse voltages, two peaks were found and are composed of different defect states. The first peak with two components was related to diffusion of Mg p -type dopants in the n -GaN and VN -related defects. The two components have activation energies close to 0.25 eV, from valence band and conduction band with a capture cross-section of ∼10 −16 cm 2 . The second peak with two components showed temperature shifts with the pulse height indicating a band-like behavior. This peak was commonly attributed to deep acceptor CN -related defects with an activation energy of E V +0.88 eV and a capture cross-section of 10 −13 cm 2 . A second acceptor level was found, with an activation energy of 0.70 eV and a capture cross-section of 10 −15 cm 2 . This second component was previously attributed to native point defects in GaN.